Evaluasi Program Penyaluran Dana Zakat, Infaq dan Shadaqah Kepada Pelaku Usaha - Sukarna, Anton; Hubeis, Musa; Suryahadi, Suryahadi (Institut Pertanian Bogor, 2023)
The role of the Amil Zakat Institution (Laznas) Berdaya Sejahtera Mandiri (BSM) for the Ummah is to manage the ZIS funds (zakat, infaq, shadaqah) as well as possible and as safely as possible in the form of programs that are beneficial to the people and have sustainable benefit values. The aims of the research are (1) to analyze the program process for channeling ZIS funds to business actors; (2) Analyzing the performance and development of program beneficiary mustahik; and (3) Predicting the development of the ZIS fund distribution program to business actors in the future. The research location was carried out at the BSM Village Program located in three villages, namely Rejosari Village, Lampung, Kedarpan Village, Purbalingga; Jati Village, Trenggalek. The research time spans seven months, from January to July 2022. Data processing uses strengths, weaknesses, opportunities and threats (SWOT)-Balanced Scorecard (BSC). The validity test analysis of the four perspectives shows valid results. Reliability test analysis on the four BSC perspectives is reliable (reliable). The results of the analysis of financial ratios, seen from the ratio of liquidity, solvency and profitability show quite healthy results, namely the program for channeling ZIS funds to business actors is running well, can run their business, and has good performance. The results of the SWOT-BSC analysis provide alternative strategies that can be carried out in the future, namely (1) A financial perspective by strengthening literacy programs and building an integrated service system to increase public trust; (2) Perspective of members by strengthening GCG and HR capacity, as well as socializing work programs to prospective muzakki; (3) Internal business process perspective by increasing internal marketing to BSI customers and standardizing SOPs so that the program runs optimally; (4) The perspective of learning and growth by conducting intensive assistance, as well as creating programs that are in line with the BSI program. The results of the analysis using the QSP matrix show that the priority strategy that can be implemented is to provide intensive assistance so that program beneficiaries become bankable